Penyelesaian Perjanjian Jual Beli Hak Atas Tanah Yang Mengandung Cacat Hukum - Gusti Ayu Kade Komalasari (Universitas Mahendradatta, 2018)
A sale and purchase agreement of a defective land, whose settlementoutside the court may be settled in a familial manner by deliberating between theparties to the sale and purchase agreement outside this court. The parties mayrequest the assistance of village officials (Village Head or lurah), lawyers ornotaries. So the settlement of a sale and purchase agreement that contains defectsoutside the court can be done in a peaceful way, meaning that between the sellerand the buyer reconcile. Regarding the defect, if the defect there is an element oftrickery, then the party who cheated in this case the buyer is entitled to claimcompensation to the seller and the seller is obliged to provide compensation to thebuyer or the object of sale and purchase is returned to the seller and accompaniedby a change loss due to the ruse performed by the seller.